Short QT interval - Rai, Bijondra Kumar (Health Renaissance, 2013)
Introduction: Short QT Interval (Short QT Syndrome) is a very rare clinical condition. An individual with short QT interval frequently presents with chest pain, palpitation, fainting attack and sometimes cardiac death. Objective: To report a case of Short QT Syndrome. Case: A 27 year old man presented with the complaint of frequent attack of chest pain, palpitation and fainting attack for last one and half years. The ECG revealed short QT interval of 300ms without any cardiac abnormalities. Conclusion: The short QT interval (Short QT Syndrome) is one of the causes of palpitation, chest pain, dizziness and syncope in a young person. Early detection is possible by doing ECG. So ECG is advised to all adults complaining of frequent chest pain, unexplained fainting attack. Health Renaissance, January-April 2013; Vol. 11 No.1; 92-94 DOI: http://dx.doi.org/10.3126/hren.v11i1.7611